2007
DOI: 10.1021/jp068285a
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural Transition in n-Pentane:  A Raman Study

Abstract: Pressure-induced Raman spectroscopy studies on n-pentane have been carried out up to 17 GPa at ambient temperature. n-Pentane undergoes a liquid-solid transition around 3.0 GPa and a solid-solid transition around 12.3 GPa. The intensity ratio of the Raman modes related to all-trans conformation (1130 cm-1 and 2850 cm-1) to that of gauche conformation (1090 cm-1 and 2922 cm-1) suggests an increase in the gauche population conformers above 12.3 GPa. This is accompanied with broadening of Raman modes above 12.3 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 34 publications
4
30
1
Order By: Relevance
“…Raman spectroscopy of phonon scattering has been widely applied to investigate crystallographic phase transitions12345; it offers an opportunity as a sensitive probe for the study of crystal structure changes. In magnetic materials, Raman spectroscopy of phonon scattering can also be applied to investigate magnetic phase transitions if spin-phonon coupling has clear influence on phonon scattering67891011.…”
mentioning
confidence: 99%
“…Raman spectroscopy of phonon scattering has been widely applied to investigate crystallographic phase transitions12345; it offers an opportunity as a sensitive probe for the study of crystal structure changes. In magnetic materials, Raman spectroscopy of phonon scattering can also be applied to investigate magnetic phase transitions if spin-phonon coupling has clear influence on phonon scattering67891011.…”
mentioning
confidence: 99%
“…To the best of our knowledge, nearly all compounds including CH 3 group(s) were observed to have a negative pressure coefficients at low pressures such as CH 3 HgM (M = Cl, Br, and I), (CH 3 ) 2 XM (X = Sn and Tl), X(CH 3 ) 4 (X = Si, Ge, and Sn), and (CH 3 ) 2 S, which is regarded as a typical character of the rotational motions of the CH 3 group. Additionally, it is found that each mode has very different pressure coefficient as shown in Table , and C–H stretch modes exhibit the most intensive pressure effects in mixed phase; the next few modes are C–Se stretch, CH 3 deformation, and C–Se–C deformation sequentially, which is reasonable for the pressure‐induced vibrational affects in a molecule except for the CH 3 deformational modes . Besides the above‐mentioned evidence for the phase transition from Phases I to II at 4.4 GPa, the evidence provided by the pressure coefficients can also be found in Figure and Table : The pressure coefficients for most of the modes show a drastic reduction compared to that in the Phase I, which possibly results from the lack of enough moveable space for the groups of DMSe with increasing pressure; however, it is of interest to note that the pressure coefficients of the CH 3 deformation modes increase slightly in Phase II, which including the pressure coefficient of the Mode ν 5 is from 2.91 in Phase I to 3.16 in Phase II, and unassigned Mode ν 5 ' is from 4.07 in Phase I to 4.44 in Phase II.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is found that each mode has very different pressure coefficient as shown in Table 1, and C-H stretch modes exhibit the most intensive pressure effects in mixed phase; the next few modes are C-Se stretch, CH 3 deformation, and C-Se-C deformation sequentially, which is reasonable for the pressure-induced vibrational affects in a molecule except for the CH 3 deformational modes. [45] Besides the above-mentioned evidence for the phase transition from Phases I to II at 4.4 GPa, the evidence provided by the pressure coefficients can also be found in Figure 3 and Table 1: The pressure coefficients for most of the modes show a drastic reduction compared to that in the Phase I, which possibly results from the lack of enough moveable space for the groups of DMSe with increasing pressure; however, it is of interest to note that the pressure coefficients of the CH 3 deformation modes increase slightly in Phase II, which including the pressure coefficient of the Mode ν 5 is from 2.91 in Phase I to 3.16 in Phase II, and unassigned Mode ν 5 ' is from 4.07 in Phase I to 4.44 in Phase II. In view of the situation here that DMSe has been crystallized in Phase II, such anomalistic pressure effects of the CH 3 deformation modes suggest perplexed behavior of the CH 3 groups in crystallized DMSe, which should lead to the changes on crystal structure with increasing pressure.…”
Section: Vibrational Properties and Phases Of Dmse Under Pressurementioning
confidence: 99%
“…The absence of hydrogen at 11 GPa is because of hydrogen diffusion or secondary reactions of hydrocarbons or graphite. The C-C vibrations of n-butane 37 , n-hexane 39 , and n-pentane 38 were detected in the spectra. In the case of the n-pentane and n-hexane, they were never detected in such types of experiments.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…[2][3][4]12 , for unsaturated compounds the reference peaks were obtained from 31,32 , and for graphite (soot) modes, the reference peaks were obtained from 27,28 . The reference peaks for C-C stretching and C-C bending of hydrocarbons were obtained for ethane from 12 , the peaks for propane were obtained from 12,37 , the peaks for n-butane from 12,37 , the peaks for n-pentane from 39 , and the peaks for n-hexane were obtained from 38 . The propane remained stable at 930 K. The spectra of untouched propane are in good correspondence with the previous experiments we carried out 37 .…”
Section: Figurementioning
confidence: 99%